INOVASI MANAJEMEN DAKWAH DI ERA DIGITAL PADA KOMUNITAS HIJRAH BOOSTERS - Alfiani; Qudratullah; Alfiani, Alfiani; Qudratullah, Qudratullah (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2025)
This study aims to analyze the innovation of dakwah management in the digital era implemented by the Hijrah Boosters community, an active dakwah group that utilizes modern communication technologies. Using a descriptive qualitative approach, this research examines the strategies adopted by the community in leveraging social media to disseminate Islamic messages relevant to younger generations. Data were collected through online activity observations, content analysis, and in-depth interviews with community administrators. The findings reveal that Hijrah Boosters adopt various innovations, including the use of popular platforms such as Instagram, Facebook, and Threads, combined with interactive features such as live streaming, polls, reels, and interactive stories. These strategies are designed to build sustained audience engagement and expand dakwah outreach. The community also implements structured content management, including material planning, consistent posting schedules, and routine evaluations of audience responses. Nevertheless, the community faces several challenges, including competition from other dakwah content and changes in social media algorithms that affect content visibility. These challenges are addressed through data-driven strategy adjustments, improving visual and message quality, and collaborating with public figures or other communities to expand networks. This study provides insights into the importance of innovation, adaptation, and consistency in digital dakwah. The findings also affirm that successful dakwah in the modern era greatly depends on the ability to manage digital media creatively and respond effectively to the dynamics of the platforms used.